ACCESSIBLE TOURISM: EXAMPLES AND GOOD PRACTICES IN SELECTED COUNTRIES FROM EUROPE - Milena TALESKA, Dejan METODIJESKI, Jasmina ANDREEVA, Nikola CUCULESKI (TURISTIKA, 2021)
Tourism is an activity of people who travel outside their permanent place of residence, and today is a phenomenon that is present in all countries of the world and is growing more globally. Inclusion, disability, world aging and tourism are important fields of research, as they have implications for the supply and demand of tourism products and services. The subject of this paper is accessible tourism and a review of good examples and practices in selected European countries. The paper presents the basic aspects of accessible tourism and various initiatives related to this type of tourism in Europe. For the purposes of the paper, research methodology and secondary data sources were used by consulting relevant literature related to accessible tourism as well as the Internet. An analysis and review of examples of accessible tourism was made, based on a systematic evaluation of their content and activities. The concluding observations refer to the use of successful examples and practices from the developed tourist countries in Europe, in order to improve the conditions for accessible tourism in other countries.
Keywords: Keywords: tourism, accessibility, disability, Europe